2014
DOI: 10.1039/c3sc52030g
|View full text |Cite
|
Sign up to set email alerts
|

New evidence for 5f covalency in actinocenes determined from carbon K-edge XAS and electronic structure theory

Abstract: Evidence for metal-carbon orbital mixing in thorocene and uranocene was determined from DFT calculations and carbon K-edge X-ray absorption spectra (XAS) collected with a scanning transmission X-ray microscope (STXM). Both the experimental and computational results showed that the 5f orbitals engaged in significant d-type mixing with the C 8 H 8 2À ligands, which increased as the 5f orbitals dropped in energy on moving from Th 4+ to U 4+. The first experimental evidence for extensive f-orbital interactions has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
214
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 141 publications
(230 citation statements)
references
References 89 publications
12
214
2
Order By: Relevance
“…Both features were well resolved from the rising edge, which had an inflection point of 2825.7 eV. The large peak area (defined hereafter as peak intensity) of 0.70 (7) for the B-feature was comparable to that of the A-feature at 0.84 (8). The spectra from the LnCl 6 3− (formally Ln III ) were similar to that obtained from CeCl 6 2− in that they also contained intense A-features near the rising edge (∼2824 eV; aqua trace in Figure 11) with intensities ranging from 0.93(9) to 0.48 (5).…”
Section: ■ Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Both features were well resolved from the rising edge, which had an inflection point of 2825.7 eV. The large peak area (defined hereafter as peak intensity) of 0.70 (7) for the B-feature was comparable to that of the A-feature at 0.84 (8). The spectra from the LnCl 6 3− (formally Ln III ) were similar to that obtained from CeCl 6 2− in that they also contained intense A-features near the rising edge (∼2824 eV; aqua trace in Figure 11) with intensities ranging from 0.93(9) to 0.48 (5).…”
Section: ■ Introductionmentioning
confidence: 93%
“…For example, although the intensities of 0.93 (9) for Ce III and 0.83 (8) for Nd III were equivalent once the error was considered ( Table 2 and Figure 11), marked intensity decreases were observed when non-adjacent lanthanides on the periodic table were compared. The most extreme example was associated with the decrease from 0.93 (9) in Ce III to 0.48 (5) for Gd III .…”
Section: ■ Introductionmentioning
confidence: 93%
“…This is especially true if future studies validate the generality of the conclusions described here on how M–E electronic structure and orbital mixing vary as the metal identity changes. Hence, our efforts will continue to focus on evaluating M–O vs. M–S bonding in both the solution- and solid-state for even heavier metals, namely lanthanide and actinide elements, 41,58,59,83,85,87 where f- and d-orbital contributions to covalency are anticipated.…”
Section: Outlook and Conclusionmentioning
confidence: 99%
“…The results highlighted two contrasting trends in orbital mixing from one pair of highly symmetric molecules, and showed that covalency does not increase uniformly for different molecular orbital interactions with later actinides. [166] Thorocene (= Th(COT) 2 ) adducts of the neutral 2,2'-bipyridine and its radical anion have been investigated. Thorocene readily reacted with 2,2'-bipyridine to afford Th(COT) 2 (κ 2 -bipy), which has an unusual bent geometry.…”
Section: Other Organolanthanide-catalyzed Reactionsmentioning
confidence: 99%